2018
DOI: 10.12968/bjon.2018.27.7.358
|View full text |Cite
|
Sign up to set email alerts
|

Caring for patients with dementia in the acute care setting

Abstract: This article highlights the vulnerability of people with dementia in the acute hospital setting, where they are more likely to experience clinical incidents such as falls, contract infections and be prescribed neuroleptic drugs. This patient group has a significantly longer length of hospital stay and higher mortality rate following discharge compared with those without dementia. As many as one third are discharged to institutionalised care. The article explores the knowledge gap concerning the complexity of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Similarly, isolated patients are at a higher risk of AEs such as hospital-acquired pressure ulcers [ 37 ]. Our findings are also consistent with previous studies showing that mental status impairments are associated with hospital-acquired complications [ 38 , 39 ]. Furthermore, other studies have shown that frail people admitted to hospitals can develop geriatric syndromes, with a higher occurrence of CCIF such as communication disorders, incontinence, vascular fragility or nutritional syndromes [ 4 , 11 , 40 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, isolated patients are at a higher risk of AEs such as hospital-acquired pressure ulcers [ 37 ]. Our findings are also consistent with previous studies showing that mental status impairments are associated with hospital-acquired complications [ 38 , 39 ]. Furthermore, other studies have shown that frail people admitted to hospitals can develop geriatric syndromes, with a higher occurrence of CCIF such as communication disorders, incontinence, vascular fragility or nutritional syndromes [ 4 , 11 , 40 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…In doing so, Dr. Alzheimer was credited for the discovery of the first of the Alzheimer's disease incidents (Ferri et al, 2005). Dementia has severe symptoms that include progressive memory loss, the inability to communicate/ reason, and a drastic change in personality (Butcher, 2018 Most notably, throughout the years, the Honduras' government has made significant improvements to the public health system. In Figure 1…”
Section: B) Honduras; Public Health Policy Discussionmentioning
confidence: 99%
“…Some studies explored the current state of health assistance for older people with dementia in the acute care setting but without mention to the integrated care pathway. Although there was an increase in the development and use of these pathways in the acute settings [62][63][64], however some concerns have emerged. In fact, there is still an insufficient evidence to support the effectiveness of these pathways in the acute setting and more studies should be encouraged.…”
Section: Discussionmentioning
confidence: 99%